Maria Lipowska (1913–1985) – Sketches for Biography - Wałęga, Agnieszka (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The aim of the article is to remind the figure of Maria Lipowska – associated with pedagogy on The Nicolaus Copernicus University in Toruń in the years 1945–1983. This paper is part of the study on restoring the history of women working at the University in Toruń. In the literature so far there have been no broader studies devoted to this character. Based on the source materials collected in the Archive of the Nicolaus Copernicus University in Toruń, in the context of changes in Polish higher education, Lipowska was presented, indicating her significant contribution to the development of pedagogy in Toruń especially in the didactic and organizational area.